ACS-22, a protein homologous to mammalian fatty acid transport protein 4, is essential for the control of the toxicity and translocation of multi-walled carbon nanotubes in Caenorhabditis elegans. Issue 5 (8th January 2016) - Zhi, Lingtong; Fu, Wei; Wang, Xiong; Wang, Dayong
Abstract : ACS-22 plays an essential role in regulating toxicity and translocation of MWCNTs. Abstract : Biodistribution and translocation are important for the generation of the toxicity of multi-walled carbon nanotubes (MWCNTs) in organisms. However, we know little about the molecular mechanisms of MWCNT translocation. In Caenorhabditis elegans, the acs-22 gene encodes a protein homologous to mammalian FATP4 (fatty acid transport protein 4). In this study, we employed a C. elegans in vivo assay system to investigate the possible function of ACS-22 in regulating the toxicity and translocation of MWCNTs. Prolonged exposure to MWCNTs significantly decreased transcriptional expression of the acs-22 gene. Loss-of-function mutation of the acs-22 gene strengthened MWCNT toxicity to the functions of both primary targeted organs such as intestine and secondary targeted organs such as neurons and reproductive organs; however, overexpression of the acs-22 gene reduced the toxicity of MWCNTs to the functions of both primary and secondary targeted organs. Loss-of-function mutation of the acs-22 gene enhanced the distribution and translocation of MWCNTs in both primary and secondary targeted organs, whereas overexpression of the acs-22 gene inhibited the distribution of MWCNTs in primary targeted organs and prevented translocation of MWCNTs into secondary targeted organs. Moreover, our results demonstrated the important function of ACS-22 in intestine to be in limiting the toxicity and translocation of MWCNTs. Therefore, our data suggest an essential role of ACS-22 in regulating the toxicity and translocation of MWCNTs in nematodes. Our results will provide important clues for further examination of the molecular mechanisms of translocation of MWCNTs in organisms.